1996
DOI: 10.1083/jcb.132.1.137
|View full text |Cite
|
Sign up to set email alerts
|

BED1, a gene encoding a galactosyltransferase homologue, is required for polarized growth and efficient bud emergence in Saccharomyces cerevisiae.

Abstract: Abstract. The ellipsoidal shape of the yeast Saccharomyces cerevisiae is the result of successive isotropic/apical growth switches that are regulated in a cell cycledependent manner. It is thought that growth polarity is governed by the remodeling of the actin cytoskeleton that is itself under the control of the cell cycle machinery. The cell cycle and the morphogenesis cycle are tightly coupled and it has been recently suggested that a morphogenesis/polarity checkpoint control monitors bud emergence in order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 37 publications
(59 reference statements)
2
38
0
Order By: Relevance
“…This includes a mutation (bed1 or mnn10) that delays budding by affecting protein glycosylation without overtly perturbing actin organization (Mondesert and Reed 1996;Theesfeld et al 2003). Thus, it seems possible that the checkpoint monitors bud emergence and delays Clb1,2p-Cdc28p activation when there is no bud.…”
Section: Regulation Of Cdc28p Tyrosine Phosphorylation In Response Tomentioning
confidence: 99%
“…This includes a mutation (bed1 or mnn10) that delays budding by affecting protein glycosylation without overtly perturbing actin organization (Mondesert and Reed 1996;Theesfeld et al 2003). Thus, it seems possible that the checkpoint monitors bud emergence and delays Clb1,2p-Cdc28p activation when there is no bud.…”
Section: Regulation Of Cdc28p Tyrosine Phosphorylation In Response Tomentioning
confidence: 99%
“…The following disruptions and alleles are described in the cited publications: cla4::TRP1 (Benton et al, 1997); gin4-⌬9 (Longtine et al, 1998a); hsl1::URA3 (Ma et al, 1996); mih1::LEU2 (Russell et al, 1989); bed1::URA3 (Mondesert and Reed, 1996); nap1::kan r , HSL7-HA:kan r , and cdc12-6::LEU2 (Longtine et al, 2000); HSL1-13myc::URA3 (McMillan et al, 1999); hsl1 K110R -13myc (Theesfeld et al, 2003); and CDC3-GFP (Caviston et al, 2003). elm1::LEU2 and mih1::TRP1 disruptions were generated by the one-step PCR-based method (Baudin et al, 1993) using pRS305 and pRS304 (Sikorski and Hieter, 1989) as template.…”
Section: Yeast Strains and Plasmidsmentioning
confidence: 99%
“…Moreover, cells lacking Pmr1 show genetic interactions with the cell polarity GTPase, Cdc42 (68). Several reports have shown that mannosyltransferase mutants affected in N-glycosylation are defective in polarized growth and become dependent on an intact mitotic checkpoint for survival, which provides time to produce a bud (56,57). Overriding the morphogenesis checkpoint by Clb2 overexpression in these mutants resembles the multinucleation phenotype of pmr1⌬ swe1⌬ mutants (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that mannosyltransferase mutants affected in N-glycosylation are defective in polarized growth and become dependent on an intact mitotic checkpoint for survival, which provides time to produce a bud (56,57). Overriding the morphogenesis checkpoint by Clb2 overexpression in these mutants resembles the multinucleation phenotype of pmr1⌬ swe1⌬ mutants (56,57). The fact that some components of the cis-Golgi mannosyltransferase complex are Mn 2ϩ -dependent enzymes suggests that the function of these enzymes is impaired if the Golgi is not supplied with Mn 2ϩ (53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation